Ecotourism as a tool in salt lick conservation - Ang , Sek Chuan; Chan , Ngai Weng (Environmental Management Society, Malaysia, 2011)
This study was conducted to determine whether ecotourism plays an important role in the conservation of salt licks. Salt licls has been overlooked as important component of habitat biodiversity for wildlife. A Salt lick have been taken for granted as anatural geological formation but lacking the emphasis on its significant role to the ecosystem abd wildlife. Many scientific studies on physico-chemical analysis and wildlife visitations at salt licks document their significance. Due to neglect and other reasons, many salt licks have been destroyed by development that encroached into natural landscape such as logging, poaching damming and plantation developments.However,many salt licks in national and state parks,and forest reserves have been successfully exploited for ecotourism attractions and these exploitations undeniably have benefited conservation of those salt licks. The study methodology focuses mainly on field research using empirical investigations,interviews and in-situ visits to many of the salt lick conservation sites in Malaysia. The findings show that ecotourism can be an important tool in salt lick conservation. A well managed touristic salt lick can sustain wildlife habitat and environment conservation.